Superconductivity of compressed iron: Low temperature electrical transport behaviour - Pedrazzini, Pablo; Sengupta, K.; Pedrazzini, P.; Jaccard, D. (IOP Publishing, 2010)
Fil: Pedrazzini, P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; University of Geneva; Suiza